Kinerja Keuangan BPR Syariah Ditinjau dari Aspek Pertumbuhan Ekonomi di Provinsi Lampung - Ilham Setio Wibowo; Denny Kurniawan; Sastya Putri; Tri Endang Yulianti; Harits Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to use financial indicators to determine the effect of regional gross domestic product on the performance of Sharia BPR in Lampung. This survey method uses a quantitative descriptive survey whether the performance of the Lampung BPR SYARIAH will be influenced by Lampung's economic growth between January 2020 to December 2021. The population and sample are all BPR SYARIAH registered with the Financial Services Authority (OJK), and there are 11 BPR SYARIAH in the Lampung study area. So it can be said that the influence of KAP (X1) NPF (X2) ROA (X3) BOPO (X4) FDR (X5) CASH RATIO (X6) triggers the GRDP (Y). %, the remaining 1% is caused by other unavailable factors. The result of the f-test is known as the probability statistic F (0.017600). Because (0.05), it can be said that KAP, PAP, NPF, ROA, BOPO, FDR, and CASHRATIO together have a major influence on GRDP. And the partial significance test shows the value of Prob. KAP Ha1 was rejected because 0.05 < 0.0731, indicates a negative relationship, Prob value. NPF Ha2 is accepted because 0.0191 < 0.05 indicates a positive relationship, Prob value. ROA Ha3 is accepted because 0.0681 < 0.05 indicates a positive relationship, Prob value. BOPO Ha4 is rejected because 0.1055 < 0.05 indicates a negative relationship, Prob value. FDR Ha5 is accepted because 0.0398 < 0.05 indicates a positive relationship, Prob value. CASHRASIO Ha6 is accepted because 0.0235 < 0.05 indicates a positive relationship.